Experimental and numerical investigation of bubble evolution and bubble wall fluctuation mechanism during water entry of flared cavity. (15th December 2022) - Duan, Wenyang; Shi, Zhang; Jiang, Zhen; Li, Huayang; Huang, Limin
Abstract: Most of the previous research on water entry focused on simple objects with "closed surface and regular shape", such as wedges and disks. Only a few studies have investigated the water entry of complex structures with "surface cavity and irregular shape", such as typical spacecraft, which are summarized as flared cavity in this paper. The water entry of flared cavity is a strong nonlinear process coupled with multi phase media, during which the liquid flows into or out of the flared cavity, and the obvious phenomenon of bubble wall fluctuation will appear. In this study, we experimentally investigate the bubble evolution process and bubble fluctuation law in a flared cavity under different impact speeds. The evolution process of bubble shape is photographed by a high-speed camera, and the bubble evolution process is divided into four stages: bubble formation stage, bubble development stage, bubble contraction stage and bubble shedding stage. It is found that there is an obvious fluctuation phenomenon on the bubble wall during the bubble development stage, which is mainly because of gas expansion and compression in the structural cavity, and the wall fluctuation law is basically consistent with the gas expansion and contraction trend. It is also established that the dimensionless parameters R/H1 and H1/H2 can be good indicators to describe the bubble expansion and bubble shedding, the dimensionless bubble expansion parameter R/H1 is stable between 0.033 and -0.042, and the dimensionless bubble shedding parameter H1/H2 is stable between 0.062 and -0.069. Highlights: The bubble wall fluctuation phenomenon of the flared cavity is found, the fluctuation law of the bubble wall diameter is studied, and the physical mechanism of the bubble wall fluctuation is revealed. The bubble morphological evolution and abscission law of flared cavity are explored, and its evolution mechanism is preliminarily revealed.